2002
DOI: 10.1177/014107680209501105
|View full text |Cite
|
Sign up to set email alerts
|

Illegible Handwriting in Medical Records

Abstract: SUMMARYIn clinical records many items are handwritten and difficult to read. We examined clinical histories in a representative sample of case notes from a Spanish general hospital. Two independent observers assigned legibility scores, and a third adjudicated in case of disagreement. Defects of legibility such that the whole was unclear were present in 18 (15%) of 117 reports, and were particularly frequent in records from surgical departments.Through poor handwriting, much information in medical records is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 7 publications
1
43
0
Order By: Relevance
“…Included in this information are patient demographics, progress notes, problems, medications, vital signs, past medical history, immunizations, laboratory data, and radiology reports” 7. Some of the basic benefits associated with EHRs include being able to easily access computerized records and the elimination of poor penmanship, which has historically plagued the medical chart 8,9. EHR systems can include many potential capabilities, but three particular functionalities hold great promise in improving the quality of care and reducing costs at the health care system level: clinical decision support (CDS) tools, computerized physician order entry (CPOE) systems, and health information exchange (HIE).…”
Section: Why We Need Ehrsmentioning
confidence: 99%
“…Included in this information are patient demographics, progress notes, problems, medications, vital signs, past medical history, immunizations, laboratory data, and radiology reports” 7. Some of the basic benefits associated with EHRs include being able to easily access computerized records and the elimination of poor penmanship, which has historically plagued the medical chart 8,9. EHR systems can include many potential capabilities, but three particular functionalities hold great promise in improving the quality of care and reducing costs at the health care system level: clinical decision support (CDS) tools, computerized physician order entry (CPOE) systems, and health information exchange (HIE).…”
Section: Why We Need Ehrsmentioning
confidence: 99%
“…Many studies of doctors’ written entries in medical records have been retrospective,2 3 7 8 making between-doctor comparisons difficult because the originating clinical information differs between entries. We controlled the auscultation findings presented to participants in order to compare their drawings in a way not possible with retrospective analyses of different clinical encounters.…”
Section: Discussionmentioning
confidence: 99%
“…However, the content of medical records is a potential source of miscommunication between clinicians. Doctors’ written entries in medical records have been criticised for their illegibility2 3 and ambiguity 4–8. Despite the computer revolution, as well as advances in medical imaging, much clinical information in hospital records continues to be handwritten, and some of it drawn by hand.…”
Section: Introductionmentioning
confidence: 99%
“…and Schneider et al 6 . suggest that doctors' writing is probably no worse than other professionals, Rodriguez‐Vera et al 7 . found 18% (3% in medical units, 32% in surgical units) of 117 reviewed charts contained illegible writing such that the meaning was unclear, yet Ved and Coupe 8 showed that audit and feedback can improve legibility.…”
Section: Discussionmentioning
confidence: 99%